PENGARUH POLA ASUH ORANG TUA TERHADAP KEMAMPUAN SOSIAL ANAK USIA 6-7 TAHUN - Lestiawati, I Made (JIV-Jurnal Ilmiah Visi, 2013)
This research aims to know the pattern of parenting to social child ability of age 6-7 year at SDN Menteng 02 Pagi Jakarta Pusat. Research method used by Ex Post Facto. Technique of Intake sample is cluster random sampling with the amount sample is 46 child, then conducted spreading quesioner to determine the pattern group of the autoritary and democratic parent. Technique analyze the data used to test the hypothesis is uji-t after beforehand conducted by a prerequisite test that is test the normalitas. Result of examination of normalitas data use the test Liliefors of group A that is Lacount 0,113 < Ltabel 0,173 and group B by Lacount 0,065 < Ltabel 0,173 meaning data have normal distribution. Hypothesis examination use the uji-t of level signifikansi α = 0,05 obtained tacount =94,8 bigger than ttabel = 1,68, this means hypothesis of zero (Ho) refused, so that mean hypothesis alternative (ha) it’s accepted that pattern of parenting have an effect on to social child ability. Matter of this means social ability of child is higher with the democratic parent than the autoritary parent. Result of research show there are influence which are positive significant between pattern of parenting to social child ability, where social ability of child is higher with the democratic parent than the autoritary parent. Implication from this research that pattern of the democratic parent can develop the social ability of high child as tool interaction with the area. Parent can give correct of take care so that the social ability of child is advance.